2019
DOI: 10.1002/eji.201948355
|View full text |Cite
|
Sign up to set email alerts
|

Murine CD8 T‐cell functional avidity is stable in vivo but not in vitro: Independence from homologous prime/boost time interval and antigen density

Abstract: It is known that for achieving high affinity antibody responses, vaccines must be optimized for antigen dose/density, and the prime/boost interval should be at least 4 weeks. Similar knowledge is lacking for generating high avidity T‐cell responses. The functional avidity (FA) of T cells, describing responsiveness to peptide, is associated with the quality of effector function and the protective capacity in vivo. Despite its importance, the FA is rarely determined in T‐cell vaccination studies. We addressed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…It would be of interest to decipher whether a third dose of the mRNA vaccine in healthy individuals, which is more effective against severe COVID-19-related outcomes compared to two doses 35 , also associates to increased T cell immunity. It is also of interest to examine whether differential time-intervals between the prime and booster vaccinations have impact on the magnitude and phenotype of the vaccine-elicited T cells 36 , 37 . A recent study indicated only differences for the induction of IL-2-expressing CD4 + T cell responses by mRNA vaccines when comparing intervals of 3–6 weeks to 8–16 weeks between the 1 st and 2 nd dose but shorter intervals were not compared 37 .…”
Section: Discussionmentioning
confidence: 99%
“…It would be of interest to decipher whether a third dose of the mRNA vaccine in healthy individuals, which is more effective against severe COVID-19-related outcomes compared to two doses 35 , also associates to increased T cell immunity. It is also of interest to examine whether differential time-intervals between the prime and booster vaccinations have impact on the magnitude and phenotype of the vaccine-elicited T cells 36 , 37 . A recent study indicated only differences for the induction of IL-2-expressing CD4 + T cell responses by mRNA vaccines when comparing intervals of 3–6 weeks to 8–16 weeks between the 1 st and 2 nd dose but shorter intervals were not compared 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Our first attempt to generate a COVID-19 vaccine was based on producing a recombinant RBD in human eukaryotic cells and chemically coupling the domain to CuMV TT -VLPs, resulting in a vaccine candidate that binds to ACE2 and induces neutralizing antibodies in mice [ 20 ]. Chemical coupling techniques have proven efficacious for the production of numerous vaccine candidates [ 21 , 22 , 23 , 24 , 25 ]. However, to facilitate GMP-compatible production at a large-scale, genetic fusion techniques may be considered a better option.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found similar FA irrespective of the different vaccination strategies. Moreover, FA was surprisingly stable over time in vivo [8]. There may be well‐founded reasons why T cells could profit from keeping FA stable and similar among the cells that participate in the response.…”
Section: A New Model For Explaining Fa Stability In Vivomentioning
confidence: 99%
“…TCR‐pMHC affinities are relatively weak, with K D values that may range between 100 and 1 μM, in contrast to antibodies that may reach very high affinities ( K D values 100 to 1 pM) [2]. Finally, it remains unclear whether T cells can undergo avidity maturation during the primary immune response [8]. If primary avidity maturation was established and occurred in epitope‐specific CD8 T‐cell responses, then vaccines should/could be optimized for this phenomenon to occur.…”
Section: Introductionmentioning
confidence: 99%